Performance evaluation of injectivity for water-alternating-CO2 processes in tight oil formations. (1st January 2015) - Yang, Daoyong; Song, Chengyao; Zhang, Jiguo; Zhang, Guangqing; Ji, Yanmin; Gao, Junmin
Highlights: Performance of water-alternating-CO2 process in tight oil formations is evaluated. Fluid injectivity can be improved if CO2 slug is injected first. Displacement experiments in tight oil formations are well history matched. Effects of operational parameters on fluid injectivity are examined. Abstract: Techniques have been developed to experimentally and numerically evaluate fluid injectivity and oil recovery of water-alternating-CO2 processes in tight oil formations. Experimentally, core samples collected from tight formations are utilized to conduct a series of water-alternating-CO2 flooding experiments with different water-alternating-CO2 ratios and slug sizes. The corresponding oil production, pressure drop, gas production and water production are examined throughout the experiments. Subsequently, numerical simulations are performed to history-match the experimental measurements and conduct sensitivity analysis on operational parameters (i.e., water-alternating-CO2 ratio, cycle time, and slug size) as well. Compared to waterflooding, fluid injectivity is found to be significantly improved by injecting CO2 during the water-alternating-CO2 processes in tight formations. There exists a good agreement between the experimental measurements and simulated results, indicating that the mechanisms governing water-alternating-CO2 processes in tight oil formations have been well incorporated. It is shown from sensitivity analysis that fluid injectivity is strongly dependent on slug size, water-alternating-CO2 ratio, and cycle time.